KEBIJAKAN PEMERINTAH DALAM MENGATASI PERMASALAHAN ANAK JALANAN DI PROVINSI BANGKA BELITUNG - Anwar, Saiful; Faldiansyah, Iqram; Habibi, Ichsan; Musa, Musa (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2024)
The phenomenon of street children who often dress up as punks has begun to color the scenery in several district capitals in Bangka Belitung Province. Their activities have also begun to disturb the community and disturb public order. This study examines the government's response and its efforts to overcome the phenomenon of street children. The research method uses a qualitative approach, data collection is done by observation, interviews and documentation. The results show that most of the street children who are active on the streets of the cities in Bangka Belitung Province come from outside the Bangka Belitung. The government has made various efforts to overcome this problem, but the results have not been maximized. This research concludes that the government's response to street children is still preventive.